Analisis Variasi Slice Thickness Terhadap Informasi Anatomi Potongan Axial Pada Pemeriksaan MSCT Cervical Pada Kasus Trauma - Rizki Aditya Nugroho; Jeffri Ardiyanto; Sigit Wijokongko (Poltekkes Kemenkes Semarang, 2020)
Background: One step to create a good image is by doing slice thickness reconstruction. Slice thickness is thick slices or pieces of the object checked out. The examination procedure of MSCT in case of Cervical trauma in Radiology Installation RSUD Tugurejo Semarang using slice thickness 3 mm. This contrasts with Seeram (2016), which explained that the examination of adult MSCT Cervical Spine using slice thickness between 1-2 mm. This research aims to know the difference of anatomic information resulted by 5 slice thickness variation in MSCT Cervical Spine and to find out which slice thickness can provide optimum anatomic information.Methods: The type of this research is quantitative with an experimental approach. Data is performed by reconstructing the 5 images of MSCT cervical of trauma patients using 5 slice thickness variation which is 1 mm, 1.5 mm, 2 mm, 2.5 mm and 3 mm. The final images are evaluated by two Respondents to see the differences in anatomic information and then analyzed by using a different test (Friedman Test) from the SPSS version 24.0.Results: The results showed there is a significant difference in anatomic information on the corpus, lamina, spinous process, transverse process and fragment fracture between variations in slice thickness of 1 mm, 1.5 mm, 2 mm, 2.5 mm, and 3 mm on the MSCT Cervical examination with a significance value of 0,000 or p 0.05.Conclusion: The most optimal slice thickness to provide anatomic information on the cervical MSCT examination is 1 mm slice thickness with a mean rank value of 3.64.